CUSTOMER SATISFACTION MEDIATES PRODUCT QUALITY AND PROMOTION TO CUSTOMER LOYALTY - Dwi Gemina; Ervika Arfelina Iskandar; Tini Kartini (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
ABSTRACT In the current era of globalization, the industrial business world is experiencing very rapid growth, this is due to creative and innovative ideas created by a company. This study aims to determine the direct effect, indirect effect and the total effect of product quality and promotion on consumer loyalty through customer satisfaction. The sample in this study amounted to 100 respondents carried out by proportional random sampling. The data used in this study is ordinal data which is converted into interval scale metric data using the Method of Successive Interval (MSI). Data analysis using path analysis and Sobel Test analysis through IBM SPSS Version 25.00. The results of the study show that there is a direct and positive effect of product quality and promotion on consumer satisfaction. There is a direct and positive effect of product quality and promotion on consumer loyalty. There is a direct and positive effect of consumer satisfaction on consumer loyalty. There is an indirect and positive influence on product quality and promotion, which has an indirect and positive effect on consumer loyalty through consumer satisfaction.